Contributors, risk associates, and complications of frailty in patients with chronic kidney disease: a scoping review. (October 2019) - Wu, Patrick Yihong; Chao, Chia-Ter; Chan, Ding-Cheng; Huang, Jenq-Wen; Hung, Kuan-Yu
Frailty exhibits diverse influences on health-related outcomes and represents a surrogate of increased susceptibility to harmful injuries. Patients with chronic kidney disease (CKD) are at a higher risk of accelerated biologic aging, and, in this population, the concept of frailty emerges as an instrumental measurement of physiologic reserves. However, a comprehensive description of known independent contributors to, and risk associates of, frailty in these patients remain unavailable. In the present review, original studies up to 28 February 2019 that assessed frailty in patients with all stages of CKD were retrieved and reviewed, with results extracted and summarized. By pooling 62 original investigations, 58.1% and 49.1% used cohort and cross-sectional designs, respectively. Dialysis-dependent end-stage renal disease patients ( n = 39; 62.9%) were the most commonly examined population, followed by those with nondialysis CKD ( n = 12; 19.4%) and those receiving renal transplantation ( n = 11; 17.7%). Contributors to frailty in CKD patients included sociodemographic factors, smoking, CKD severity, organ-specific comorbidities, depression, hypoalbuminemia, and low testosterone levels. Conversely, the development of frailty was potentially associated with the emergence of cardiometabolic, musculoskeletal, and cerebral complications; mental distress; and a higher risk of subsequent functional and quality-of-life impairment. Moreover, frailty in CKD patients increased healthcare utilization and consistently elevated mortality among affected ones. Based on the multitude of contributors to frailty and its diverse health influences, a multifaceted approach to manage CKD patients with frailty is needed, and its potential influences on outcomes besides mortality need to be considered.